The role of natural exosomes from SHED-MSC in immunoregulation of M0/M1 polarized macrophage cells - Fallah, Ali; Hosseinzadeh Colagar, Abasalt; Khosravi, Ayyoob; Mohammad-Hasani, Azadeh; Saeidi, Mohsen (Frontiers in Immunology, 2025)
IntroductionExosomes (EXOs) as a targeted cell-free therapy could offer a new therapeutic strategy for immune-mediated inflammatory diseases, due to their stability and ease of storage and handling. This study focused on exosomes derived from stem cells of human exfoliated deciduous teeth (SHED-MSC-EXOs) and their role in managing the balance of immunoregulatory macromolecules that play a role in the underlying immunoregulatory mechanisms in THP-1-derived M0/M1 macrophage cells.MethodsFlow cytometry confirmed the expression of CD14, CD68, CD80, and CD86 markers in these macrophages. Following morphological and survival assessments, culture supernatants from SHED-MSCs were used to isolate exosomes. Once the exosomes were verified, Calcein AM-labeled EXOs were introduced to the macrophage cells. The immunoregulatory macromolecules were assessed by analyzing surface markers, cytokine production, and pro- and antioxidant activity.ResultsMacrophages treated with exosomes exhibited immunomodulatory effects akin to those treated with dexamethasone. The levels of anti-inflammatory and antioxidant markers, including CD206, Arg-1, IL-10, TGF-β, TAC, CAT, and SOD, which act as immunosuppressive macromolecules, were elevated. In contrast, there was a reduction in pro-inflammatory and pro-oxidant markers, including CD80, CD81, IL-6R, IL-12, TNF-α, MDA, and NO, which act as immunostimulatory macromolecules (P < 0.05).DiscussionThe findings suggest that exosomes derived from SHED-MSC can skew M0/M1 macrophages to the M2 phenotype and inhibit M1 polarization. These nanovesicles, with their distinct physical properties and ability to penetrate target cells, may prove beneficial in conditions involving the depletion of M2 macrophages and M1 macrophage-induced diseases, potentially aiding in the reduction of inflammation and tissue injury.